2013
DOI: 10.1016/j.tvjl.2013.01.009
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of osteoarthritis in cats and meloxicam efficacy using objective chronic pain evaluation tools

Abstract: This study aimed to characterize osteoarthritis (OA)-related chronic pain and disability in experimental cats with naturally occurring OA. Peak vertical ground reaction force (PVF), accelerometer-based motor activity (MA) and the von Frey anesthesiometer-induced paw withdrawal threshold were used to define OA and to test the efficacy of meloxicam. A diagnosis of OA was based on radiographic and orthopedic examinations. Cats with OA (n=39) and classified as non-OA (n=6) were used to assess the reliability and s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

12
155
1
11

Year Published

2015
2015
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 92 publications
(181 citation statements)
references
References 26 publications
12
155
1
11
Order By: Relevance
“…This finding was interpreted as an increase in activity of the descending facilitatory pathways. In line with the hypersensitivity (Guillot et al, 2013) and facilitation of temporal summation (Guillot et al, 2014) observed in OA cats, the enhanced brain metabolism in the thalamus and PAG observed in OA cats may also represent increased activity of the descending facilitatory pathways.…”
Section: Discussionmentioning
confidence: 63%
See 2 more Smart Citations
“…This finding was interpreted as an increase in activity of the descending facilitatory pathways. In line with the hypersensitivity (Guillot et al, 2013) and facilitation of temporal summation (Guillot et al, 2014) observed in OA cats, the enhanced brain metabolism in the thalamus and PAG observed in OA cats may also represent increased activity of the descending facilitatory pathways.…”
Section: Discussionmentioning
confidence: 63%
“…The extent of radiographic OA was graded by a veterinary radiologist: osteophytes and enthesiophytes were scored together according to their global size (0-3); subchondral sclerosis was scored according to its extent (0-3); and joint effusion was identified and was scored as normal (0) or increased (1) (Guillot et al, , 2013. Each joint was graded and the radiographic score was defined for forelimbs and hind limbs as the sum of the score of their joints (Table 1).…”
Section: Housing and Selection Of Catsmentioning
confidence: 99%
See 1 more Smart Citation
“…The authors found that the average value of both hindlimb PFz was higher in normal cats than in cats with OA and that PFz was positively correlated with the mean motor activity, as measured by accelerometer-based activity sensors attached to the cats' collars. In a subsequent study, Guillot et al (2013) used accelerometer-based motor activity (the von Frey anesthesiometer-induced paw withdrawal threshold) and PFz measurements to characterise OA-related chronic pain and disability in 39 cats with naturally occurring OA to evaluate the efficacy of meloxicam treatment. The diagnosis of OA was confirmed by radiography and clinical examination in 29 cats and by clinical examination only in 10 cats.…”
Section: Details Of Studies Using Cats With Orthopaedic Diseasementioning
confidence: 99%
“…Osteoarthritis occurs frequently in cats, but it is rarely diagnosed (Clarke et al 2005;Lascelles 2010;Guillot et al 2013). Degenerative changes are most often observed in elbow joints, followed by hip and stifle joints (Guillot et al 2012).…”
mentioning
confidence: 99%